Efficacy of probiotic supplements on Parkinson's disease: A systematic review and meta-analysis - Xiaxia Jin; Wendi Dong; Kaile Chang; Yongmei Yan; Xiaochun Liu (Complementary Therapies in Medicine, 2024)
Objective: This study aimed to evaluate the clinical efficacy and safety of probiotics supplementation in the treatment of Parkinson's disease (PD). Methods: We searched China National Knowledge Infrastructure (CNKI), Weipu (VIP) database, Wanfang Database, Sinomed (CBM), PubMed, Embase, Cochrane library and Web of Science databases for eligible studies from inception to January 4th, 2024. Randomized controlled trials (RCTS) comparing the effects of probiotic supplements and placebo in patients with PD. Meta-analysis was conducted with the software Review Manager 5.4. The quality assessment was performed according to Cochrane risk of bias tool. Results: A total of 11 RCTs with 756 PD patients were included in this study. We found that probiotics could increase the number of complete bowel movements (CBMs) per week and improved the scores of Patient Assessment of Constipation Quality of Life Questionnaire (PAC-QOL) (SMD = 0.73, 95 % CI: 0.54 to 0.92, P < 0.00001, I2 = 45 %; SMD = − 0.79, 95 % CI: − 1.19 to − 0.39, P < 0.001, I2 = 55 %, respectively) compared with the placebo group. However, there was no significant difference between the two groups in improving fecal traits and defecation efforts in PD patients (SMD = 0.87, 95 % CI: 0.01 to 1.74, P = 0.05, I2 = 94 %; SMD = 1.24, 95 % CI: − 1.58 to 4.06, P > 0.05, I2 = 98 %, respectively). In terms of PD composite scale scores: after treatment, there was no significant difference in Movement Disorder Society-Unified-Parkinson Disease Rating Scale Ⅲ score (MDS-UPDRSⅢ) between the probiotic group and the placebo group (SMD = − 0.09, 95 % CI: − 0.35 to 0.16, P > 0.05, I2 = 0 %). Conclusions: In conclusion, based on the overall results of the available RCTs studies, our results suggested the potential value of probiotics in improving constipation symptoms in PD patients. Therefore, probiotics may be one of the adjuvant therapy for PD-related constipation patients. The findings of this study provide more proof supporting the effectiveness of probiotics, encouraging probiotics to be utilized alone or in combination with other therapies in clinical practice for PD patients. However, more well-designed RCTs with large sample sizes are required.